Suppressive Effects of Hainosan (Painongsan) against Biofilm Production by Streptococcus mutans - Masaaki Minami; Hiroshi Takase; Masayo Taira; Toshiaki Makino (MDPI AG, 2020)
Streptococcus mutans, a bacterium that causes dental plaques, forms a biofilm on tooth surfaces. This biofilm can cause gingivitis by stimulating the gingival margin. However, there is no established treatment for biofilm removal. Hainosan (Painongsan), a traditional Japanese Kampo formula, has been used to treat gingivitis. Therefore, we investigated the biofilm suppressive effects of the hainosan extract (HNS) and its components on S. mutans. We conducted scanning electron microscopy and confocal laser microscopy analyses to clarify the anti-biofilm activities of HNS and its crude drugs. We also performed a quantitative RT-PCR assay to assess the biofilm-related gene expression. HNS showed a significant dose-dependent suppressive effect on biofilm formation. Both the scanning electron microscopy and confocal laser microscopy analyses also revealed the significant inhibitory effects of the extract on biofilm formation. Transmission electron microscopy analysis showed that HNS disrupted the surface of the bacterial wall. Furthermore, HNS reduced the hydrophobicity of the bacteria, and suppressed the mRNA expression of β-glucosyltransferase (gtfB), glucosyltransferase-SI (gtfC), and fructosyltransferase (ftf). Among the constituents of hainosan, the extract of the root of Platycodon grandiflorum (PG) showed the strongest biofilm suppression effect. Platycodin D, one of the constituent natural compounds of PG, inhibited S. mutans-associated biofilm. These findings indicate that hainosan eliminates dental plaques by suppressing biofilm formation by S. mutans.